Detection of epistatic and environmental interaction QTLs for leaf orientation‐related traits in maize. (20th December 2016) - Shi, Yong; Wang, Xiaobo; Guo, Shulei; Ren, Zhenzhen; Ku, Lixia; Zhu, Yuguang; Li, Guohui; Qi, Jianshuang; Zhang, Xin; Ren, Zhaobin; Chen, Yanhui
Abstract: Leaf architecture traits in maize are quantitative and have been studied by quantitative trait loci (QTLs) mapping. However, additional QTLs for these traits require mapping and the interactions between mapped QTLs require studying because of the complicated genetic nature of these traits. To detect common QTLs and to find new ones, we investigated the maize traits of leaf angle, leaf flagging‐point length, leaf length and leaf orientation value using a set of recombinant inbred line populations and single nucleotide polymorphism markers. In total, 19 QTLs contributed 4.13–13.52% of the phenotypic effects to the corresponding traits that were mapped, and their candidate genes are provided. Common and major QTLs have also been detected. All of the QTLs showed significant additive effects and non‐significant additive × environment effects in combined environments. The majority showed additive × additive epistasis effects and non‐significant QTL × environment effects under single environments. Common and major QTLs provided information for fine mapping and gene cloning, and SNP markers can be used for marker‐assisted selection breeding.